Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure, let's solve the given system of equations step-by-step. The equations are:
[tex]\[ \begin{cases} 3(2^x) + 3y - 2 = 25 \\ 2^x - 3y + 1 = -19 \end{cases} \][/tex]
### Step 1: Simplify the equations
First, we'll simplify both equations by isolating the constants.
Equation 1:
[tex]\[ 3(2^x) + 3y - 2 = 25 \][/tex]
Add 2 to both sides:
[tex]\[ 3(2^x) + 3y = 27 \][/tex]
Divide everything by 3:
[tex]\[ 2^x + y = 9 \][/tex]
This is our simplified first equation.
Equation 2:
[tex]\[ 2^x - 3y + 1 = -19 \][/tex]
Subtract 1 from both sides:
[tex]\[ 2^x - 3y = -20 \][/tex]
### Step 2: Solve for [tex]\(2^x\)[/tex]
Now we have the system:
[tex]\[ \begin{cases} 2^x + y = 9 \\ 2^x - 3y = -20 \end{cases} \][/tex]
Let's denote [tex]\(2^x\)[/tex] by [tex]\(a\)[/tex] for convenience:
[tex]\[ \begin{cases} a + y = 9 \\ a - 3y = -20 \end{cases} \][/tex]
### Step 3: Solve the first equation for [tex]\(y\)[/tex]
From the first equation:
[tex]\[ a + y = 9 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = 9 - a \][/tex]
### Step 4: Substitute [tex]\(y\)[/tex] into the second equation
Substitute [tex]\(y = 9 - a\)[/tex] into the second equation [tex]\(a - 3y = -20\)[/tex]:
[tex]\[ a - 3(9 - a) = -20 \][/tex]
Distribute and simplify:
[tex]\[ a - 27 + 3a = -20 \][/tex]
Combine like terms:
[tex]\[ 4a - 27 = -20 \][/tex]
Add 27 to both sides:
[tex]\[ 4a = 7 \][/tex]
Divide by 4:
[tex]\[ a = \frac{7}{4} \][/tex]
### Step 5: Substitute [tex]\(a\)[/tex] back to find [tex]\(x\)[/tex]
Recall that [tex]\(a = 2^x\)[/tex]:
[tex]\[ 2^x = \frac{7}{4} \][/tex]
By taking the logarithm base 2 of both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \log_2\left(\frac{7}{4}\right) \][/tex]
### Step 6: Find the value of [tex]\(y\)[/tex]
We already have [tex]\(y = 9 - a\)[/tex]:
[tex]\[ y = 9 - \frac{7}{4} \][/tex]
Convert 9 to a fraction with a denominator of 4:
[tex]\[ 9 = \frac{36}{4} \][/tex]
Now subtract:
[tex]\[ y = \frac{36}{4} - \frac{7}{4} = \frac{29}{4} \][/tex]
### Conclusion
So, the solutions to the system of equations are:
[tex]\[ x = \log_2\left(\frac{7}{4}\right) \][/tex]
and
[tex]\[ y = \frac{29}{4} \][/tex]
The simplified form can be written as:
[tex]\[ (x, y) \approx \left(-2 + \log_2(7), \frac{29}{4}\right) \][/tex]
[tex]\[ \begin{cases} 3(2^x) + 3y - 2 = 25 \\ 2^x - 3y + 1 = -19 \end{cases} \][/tex]
### Step 1: Simplify the equations
First, we'll simplify both equations by isolating the constants.
Equation 1:
[tex]\[ 3(2^x) + 3y - 2 = 25 \][/tex]
Add 2 to both sides:
[tex]\[ 3(2^x) + 3y = 27 \][/tex]
Divide everything by 3:
[tex]\[ 2^x + y = 9 \][/tex]
This is our simplified first equation.
Equation 2:
[tex]\[ 2^x - 3y + 1 = -19 \][/tex]
Subtract 1 from both sides:
[tex]\[ 2^x - 3y = -20 \][/tex]
### Step 2: Solve for [tex]\(2^x\)[/tex]
Now we have the system:
[tex]\[ \begin{cases} 2^x + y = 9 \\ 2^x - 3y = -20 \end{cases} \][/tex]
Let's denote [tex]\(2^x\)[/tex] by [tex]\(a\)[/tex] for convenience:
[tex]\[ \begin{cases} a + y = 9 \\ a - 3y = -20 \end{cases} \][/tex]
### Step 3: Solve the first equation for [tex]\(y\)[/tex]
From the first equation:
[tex]\[ a + y = 9 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = 9 - a \][/tex]
### Step 4: Substitute [tex]\(y\)[/tex] into the second equation
Substitute [tex]\(y = 9 - a\)[/tex] into the second equation [tex]\(a - 3y = -20\)[/tex]:
[tex]\[ a - 3(9 - a) = -20 \][/tex]
Distribute and simplify:
[tex]\[ a - 27 + 3a = -20 \][/tex]
Combine like terms:
[tex]\[ 4a - 27 = -20 \][/tex]
Add 27 to both sides:
[tex]\[ 4a = 7 \][/tex]
Divide by 4:
[tex]\[ a = \frac{7}{4} \][/tex]
### Step 5: Substitute [tex]\(a\)[/tex] back to find [tex]\(x\)[/tex]
Recall that [tex]\(a = 2^x\)[/tex]:
[tex]\[ 2^x = \frac{7}{4} \][/tex]
By taking the logarithm base 2 of both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \log_2\left(\frac{7}{4}\right) \][/tex]
### Step 6: Find the value of [tex]\(y\)[/tex]
We already have [tex]\(y = 9 - a\)[/tex]:
[tex]\[ y = 9 - \frac{7}{4} \][/tex]
Convert 9 to a fraction with a denominator of 4:
[tex]\[ 9 = \frac{36}{4} \][/tex]
Now subtract:
[tex]\[ y = \frac{36}{4} - \frac{7}{4} = \frac{29}{4} \][/tex]
### Conclusion
So, the solutions to the system of equations are:
[tex]\[ x = \log_2\left(\frac{7}{4}\right) \][/tex]
and
[tex]\[ y = \frac{29}{4} \][/tex]
The simplified form can be written as:
[tex]\[ (x, y) \approx \left(-2 + \log_2(7), \frac{29}{4}\right) \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.